Long-term water immersion of dental composites based on bioactive glass - Gajski, Petra; Par, Matej; Haugen, Håvard J.; Hildebrand, Torben; Zheng, Kai; Boccaccini, Aldo R.; Tarle, Zrinka; Marovic, Danijela (Scientific Reports, 2025)
This study investigated the effect of copper-doped mesoporous bioactive glass nanospheres (Cu-MBGN) on water sorption, solubility and porosity of an experimental dental composite over 180 days of water immersion, comparing it to bioactive glass 45S5 (BG) or inert fillers. Composites contained 35wt% Bis-GMA/TEGDMA resin (60/40), 55wt% silanised barium-glass fillers, and 10wt% of either Cu-MBGN (10-CuBG), 45S5 bioactive glass (10-BG), or inert silica nanofillers (10-Si). Both BG composites showed a higher mass increase during water immersion than inert control (10-Si) at all measured time points (p < 0.001), ranked as 10-BG > 10-CuBG > 10-Si. After 30 days, 10-BG had the greatest mass increase (4.02 ± 0.21%), followed by a decline until 180 days, while 10-CuBG (1.67 ± 0.10%) and 10-Si (1.19 ± 0.07%) showed gradual mass increases until the end of the measurement. 10-BG displayed higher water sorption and solubility than other materials, while 10-CuBG had the highest porosity parameters. While 10-BG and 10-Si showed significant increases in both total and open porosity after water immersion, no such changes were observed for 10-CuBG. The pore characteristics of dry specimens did not affect final water sorption and solubility after 180 days of water immersion. The Cu-MBGN composite had a lower mass increase than commercial BG and met ISO 4049 standards for both water sorption and solubility.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Bioactive glass; Dental materials; Experimental resin composites; Porosity; Solubility; Water sorption